Low Cost Pulse Oximeter in Outpatient Department to Detect Severity of Respiratory Infection: Retrospective Study - H, Sandeep; Uplaonkar, Vinod (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: On an average, children below 5 years of age suffer about 5 episodes of ARI per child per year, thus accounting for about 238 million attacks. ARI is responsible for about 30-50% of visits to hospital under 5-mortality rate, pneumonia consists 19% of deaths as compared to diarrhea (17%), measles (4%). This reduction in death rate in diarrhea is due to cheap and effective oral rehydration therapy diseases. Subjects and Methods: The study was conducted over period of one year from feb 2017 to feb 2018, overall hospitalized children with age group from 2months-60 months were included in the present study. Children who were with respiratory complaints like fever, cough, breathing difficulty were included. Results: In present study, all the children presenting with respiratory symptoms were analyzed and pulse oximeter were used when clinical findings were in conclusive for hospitalization. Conclusion: It was found that hypoxemia was common in patients with ALRI more show in infants then in children.